2024
DOI: 10.3389/fnins.2024.1378619
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex effects on paired-pulse suppression and prepulse inhibition of auditory evoked potentials

Koji Inui,
Nobuyuki Takeuchi,
Bayasgalan Borgil
et al.

Abstract: Responses to a sensory stimulus are inhibited by a preceding stimulus; if the two stimuli are identical, paired-pulse suppression (PPS) occurs; if the preceding stimulus is too weak to reliably elicit the target response, prepulse inhibition (PPI) occurs. PPS and PPI represent excitability changes in neural circuits induced by the first stimulus, but involve different mechanisms and are impaired in different diseases, e.g., impaired PPS in schizophrenia and Alzheimer’s disease and impaired PPI in schizophrenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…Although such effects were not observed in this study, the sample size was insufficient to exclude such possibilities. Such biases are not remote as previous paired pulse or prepulse inhibition studies reported these factors significantly affecting the degree of inhibition ( Swerdlow et al, 1993 ; Kumari et al, 2010 ; Inui et al, 2024 ). The significant potentiation of the response at 5-and 10-ms PTIs are consistent with a previous study showing paired pulse stimulation to the supraorbital nerve augmented R1 at these PTIs ( Kimura and Harada, 1976 ).…”
Section: Discussionmentioning
confidence: 91%
“…Although such effects were not observed in this study, the sample size was insufficient to exclude such possibilities. Such biases are not remote as previous paired pulse or prepulse inhibition studies reported these factors significantly affecting the degree of inhibition ( Swerdlow et al, 1993 ; Kumari et al, 2010 ; Inui et al, 2024 ). The significant potentiation of the response at 5-and 10-ms PTIs are consistent with a previous study showing paired pulse stimulation to the supraorbital nerve augmented R1 at these PTIs ( Kimura and Harada, 1976 ).…”
Section: Discussionmentioning
confidence: 91%